2019
DOI: 10.1021/acsanm.9b01416
|View full text |Cite
|
Sign up to set email alerts
|

Improved CO Oxidation via Surface Stabilization of Ceria Nanoparticles Induced by Rare-Earth Metal Dopants

Abstract: Rare earth (RE) metals have often been used as dopants to improve the catalytic activity of ceria. However, their exact role in the activity of ceria catalyst has not been clearly identified. Combining experimental and theoretical approaches, we extensively investigate CO oxidation as a model reaction on RE-doped ceria (REC). The apparent activity is linearly proportional to the specific surface area (A S), which is enlarged by RE dopants as a consequence of surface stabilization. To decouple the effect of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…Deactivation of catalysts suggests loss of active surface due to metal sintering (coalescence of particles, and particle growth), phase transformation, and pore elimination . As mentioned above, RE dopants lower surface energy, leading to smaller particle sizes . In addition, the excellence of the co‐doping system has been established in previous studies.…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 76%
See 4 more Smart Citations
“…Deactivation of catalysts suggests loss of active surface due to metal sintering (coalescence of particles, and particle growth), phase transformation, and pore elimination . As mentioned above, RE dopants lower surface energy, leading to smaller particle sizes . In addition, the excellence of the co‐doping system has been established in previous studies.…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 76%
“…Studies showed that RDC catalysts form a higher number of defect sites on the catalyst surface than pure CeO 2 , and these defect sites are directly related to catalytic activity . Therefore, regardless of the dopant, it is true that CO oxidation is affected by defect sites, but specifically, RDC catalysts create high density of defect sites by the increased surface area, thereby enhancing the CO oxidation activity . As shown in Figure a, the catalytic activity of RDC increases linearly with the increase in specific surface area.…”
Section: Improving Co Oxidation By Enhancing the Intrinsic Activity Omentioning
confidence: 98%
See 3 more Smart Citations